Mortality with musculoskeletal disorders as underlying cause in Sweden 1997-2013: a time trend aggregate level study. Issue 1 (December 2016) - Kiadaliri, Aliasghar; Englund, Martin
Abstract Background The aim was to assess time trend of mortality with musculoskeletal disorders (MSD) as underlying cause of death in Sweden from 1997 to 2013. Methods We obtained data on MSD as underlying cause of death across age and sex groups from the National Board of Health and Welfare's Cause of Death Register. Age-standardized mortality rates per million population for all MSD, its six major subgroups, and all other ICD-10 (International Classification of Disease) chapters were calculated. We computed the average annual percent change (AAPC) in the mortality rates across age/sex groups using joinpoint regression analysis by fitting a regression line to the natural logarithm of the age-standardized mortality rates and calendar year as a predictor. Results There were a total of 7 976 deaths (0.5 % of all causes deaths) with MSD as the underlying cause of death (32.5 % of these deaths caused by rheumatoid arthritis [RA]). The overall age-standardized mortality rates (95 % CI) were 16.0 (15.4 to 16.7) and 24.9 (24.1 to 25.7) per million among men and women, respectively (women/men rate ratio 1.55; 95%CI 1.47 to 1.63). On average, mortality rate declined by 2.3 % per year and only circulatory system mortality had a more favourable decline than mortality with MSD as underlying cause. Among MSD the highest decline was observed in RA (3.7 % per year) during study period. Across age groups, while there were generally stable or declining trends, spondylopathies and osteoporosis mortality among people ≥ 75 years increased by 2 and 1.5 % per year, respectively. Conclusion In overall, mortality with MSD as underlying cause has declined in Sweden over last two decades, with the highest decline for RA. However, there are variations across MSD subgroups which warrants further investigations.